Peningkatan Ketertarikan Siswa terhadap Materi IPS melalui Penggunaan Media Pembelajaran yang Variatif di Kelas 3 SD Pembangunan Laboratorium UNP - Iyai, Yustina; Zahara, Leni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to increase student interest in Social Studies (IPS) through the use of varied learning media in third-grade students at SD Pembangunan Laboratorium UNP. The typically boring nature of Social Studies learning can be addressed by presenting engaging media tailored to student characteristics. Varied learning media, such as educational videos, images, interactive games, and props, are expected to engage students, engage them, and enhance their understanding of the material. This study used a qualitative approach through observation and interviews to determine students' responses to the use of these media. The results showed that the use of diverse learning media increased student motivation and interest in Social Studies lessons. Students appeared more enthusiastic in discussions, asking questions, and completing assigned assignments. Thus, the use of varied media not only increased student interest but also strengthened their understanding of the material presented. This study recommends that educators at SD Pembangunan Laboratorium UNP optimize the use of varied learning media to improve the quality of Social Studies learning, thereby making the teaching and learning process more enjoyable and effective.